2023
DOI: 10.3390/rs15041057
|View full text |Cite
|
Sign up to set email alerts
|

Combining Remote Sensing Approaches for Detecting Marks of Archaeological and Demolished Constructions in Cahokia’s Grand Plaza, Southwestern Illinois

Abstract: Remote sensing data are increasingly being used in digital archaeology for the potential non-invasive detection of archaeological remains. The purpose of this research is to evaluate the capability of standalone (LiDAR and aerial photogrammetry) and integration/fusion remote sensing approaches in improving the prospecting and interpretation of archaeological remains in Cahokia’s Grand Plaza. Cahokia Mounds is an ancient area; it was the largest settlement of the Mississippian culture located in southwestern Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…To fill the knowledge gaps, our recent study (2023) led by Kadhim et al [ 19 ] demonstrated a detailed workflow to investigate the potential of applying standalone, integration, and fusion approaches in detecting and recording archaeological remains of Cahokia’s Grand Plaza, Southwestern Illinois, based on aerial photogrammetry and LiDAR data. We argue that there is a high possibility that this investigation could make considerable further contributions to archaeological practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To fill the knowledge gaps, our recent study (2023) led by Kadhim et al [ 19 ] demonstrated a detailed workflow to investigate the potential of applying standalone, integration, and fusion approaches in detecting and recording archaeological remains of Cahokia’s Grand Plaza, Southwestern Illinois, based on aerial photogrammetry and LiDAR data. We argue that there is a high possibility that this investigation could make considerable further contributions to archaeological practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have referred to combination, integration, fusion, and blending/merging terms as interchangeable terms. The research led by Kadhim et al [ 19 ] referred to the fusion approach as a combination of 2D images with digital models (DSM/DTM) to create a fused model. In contrast, the term integration denotes a combination of raster images (2.5D image) derived from two different sources (LiDAR and photogrammetry).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to carefully consider the effectiveness of research methods in obtaining 3D digital data. With the advancement of technology, photogrammetry, and LiDAR techniques have been widely accepted in documentation studies as they can create a digital model that closely resembles physical geometry (Luhmann et al, 2020;Kadhim et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, due to the large size of most heritage structures, complete data cannot be obtained using a single method. Experts in the eld argue that complete 3D data can be obtained by using multiple data collection techniques, also known as data integration, to avoid incomplete data (Chatzistamatis et al, 2018;Luhmann et al, 2019;Luhmann et al, 2020;Palčák et al, 2022;Kadhim et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation